Effectiveness of Posterior Decompression and Internal Fixation in Emergency Management of Thoracolumbar Fractures Complicated by Spinal Cord Injury - Jian Li; Tao Zhou; Sen Lin; Hongliang Wang (Emergency Medicine International)
Conclusion: Posterior decompression and internal fixation significantly improve spinal stability, pain, motor, and sensory functions in patients with thoracolumbar fractures and spinal cord injuries, demonstrating its effectiveness and clinical utility.